The Perception of Neighbour in CMLL Publicistics - Vaičiulytė-Semėnienė, Loreta (Vilnius University Open Series, 2021)
This article deals with the content of neighbour on the basis of the forms of the noun ‘neighbour’ (Lith. kaimynas). Efforts are made to strike a balance between the structural and the cognitive approach to its meaning. The sample base for the study consists of 700 published sentences sourced in the Corpus of the Modern Lithuanian Language (CMLL) compiled by the Centre for Computational Linguistics at the Vytautas Magnus University in Kaunas.The study has revealed a neighbour to be someone who experiences a certain mental state, someone who, in his or her (un)favourable response to the environment, affects another person in a relatively close space. Emotionally charged, this effect shows a neighbour who is a nice or a bad person to live next-doors with. The (dis)harmony of attitudes, values, and actions grounded on an (un)favourable mind-set defines a dynamic coexistenceof neighbours, or a failure to coexist.When it comes to the perception of neighbour that shifts in time, what matters is the shared space of the neighbours that has its relative boundaries and is measured as a distance – the closeness resulting in the distinction between a close > distant neighbour; yet even more important is the camaraderie – the proximity of attitudes, values, and the actions that they define – something that the dictionary definitions of the word neighbour tend to omit – and the related gradational differences between a homey > strange neighbour. When it comes to building and maintaining proximity, it is the neighbour’s temper, polite and supportive interaction, and behaviour that favours another person, such as sharing things with them and all kinds of assistance, especially in need, that matters. As the mind-sets, values, and behaviours assimilate, the neighbours become one – they become homey to each other. And the axis of oneness grounded on favour in neighbourhood is God.
Keywords: noun neighbour; concept; structural semantics